Comparison of mortality due to critical illnesses in the EU countries - Kopecká, Lucie; Jindrová, Pavla (Foundation of the Cracow University of Economics, 2017)
Health is a precondition for economic prosperity in each country and citizens’ health is also a core EU priority. Cancer, heart disease, diabetes, respiratory, mental and other chronic diseases represent great suffering to citizens and represent a huge costs for society and the economy. Huge differences in health and health care exist between and within EU countries and regions. The aim of this article is to present the results of applying of multivariate statistical methods, such as correlation analysis, component analysis, cluster analysis and multidimensional comparative analysis, and to provide an overview of the gravity of the situation in mortality from the serious diseases by the selected indicators, their various causal relations and regional differences and similarities in EU countries. The basic source of data is the database of the World Health Organization (WHO) for Europe.
Porovnání úmrtnosti způsobené kritickými nemocemi v zemích EU
Keywords: Critical illnesses; correlation analysis; component analysis; cluster analysis; multidimensional comparative analysis.; Závažná onemocnění; korelační analýza; komponentní analýza; shluková analýza; vícerozměrná srovnávací analýza.